Advances of solid polymer electrolytes with high-voltage stability - Zishao Zhao; Weizhong Liang; Shan Su; Xiangfen Jiang; Yoshio Bando; Biao Zhang; Zengsheng Ma; Xuebin Wang (Next Materials)
The solid polymer electrolyte (SPE) is considered a promising candidate to replace commercial liquid electrolytes for the coming all-solid-state lithium batteries (ASSLBs) due to its excellent safety and mechanical properties. To fully realize the potential of SPEs for energy storage, they should be paired with high-voltage cathodes to achieve higher energy density. However, current challenges remain in matching SPEs with high-voltage cathodes, including cation-catalyzed decomposition of SPEs, electrochemical instability, inadequate mechanical contact, and the inability to suppress phase transitions in cathode materials. This paper summarizes the challenges in the development of SPEs when pairing them with high-voltage cathodes, which limit the electrochemical performance of ASSLBs. The discussed strategies focus on SPE synthesis and modification, structural improvements, and cathode-electrolyte interface (CEI) protection. Additionally, the prospects for the development of high-voltage-tolerant SPEs for ASSLBs are discussed.